“Your brain is no longer your own!”: Mass Media, Secular Religion, and Cultural Crisis in Third Republic France - Meyers, Mark (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractThis essay examines the historical and discursive process that led various elites in Third Republic France (1871–1940) to interpret the modern mass media as vehicles for new, secular forms of religious experience. It argues that this interpretation owed its origins to fin-de-siècle theories about the links between collective behaviour, hypnotic suggestion, and “religiosity.” It also demonstrates that this interpretation enjoyed cultural resonance because of the specific formal properties of new audio-visual media such as radio. Adopting the methodological framework of cultural history, this paper suggests that the symbolic relevance of the term “religion” actually expanded during this period, which is well known for its growing secularism. It thus maintains that secularization in this context was not a uniform or teleological process, but one fraught with ambiguity and complexity.